A New 2-Compartment Flow Through Cell for the Simultaneous Detection of Electrochemical Reaction Products by a Detection Electrode and Mass Spectroscopy. (1st October 2016) - Bondue, C.J.; Königshoven, P.; Baltruschat, H.
Abstract: In this article we present a novel 2-compartment flow through cell (6-electrode cell). The 6-electrode cell allows the operation of two working electrodes independent from each other one of which serves as a detection electrode. A current at the detection electrode signifies the formation of soluble species at the generator electrode. This approach is reminiscent of an RRDE arrangement. However, the 6-electrode cell allows combination of RRDE-analogue experiments with differential electrochemical mass spectroscopy (DEMS). Volatile products formed at the detection electrode, therefore, can be identified via mass spectroscopy, which is not possible with an RRDE-arrangements. At the same time it is possible to identify volatile products formed at the generator electrode. We demonstrate the application of the 6-electrode cell for the oxygen reduction reaction in Li + -containing DMSO based electrolyte. We will show that soluble products that react at the detection electrode are due to the oxidation of superoxide.